Manajemen Kurikulum Tahfizul Qur’an Dalam Peningkatan Kualitas Hafalan Siswa Raudhatul Athfal - Rohimatul Bayani Tanjung (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
This study aims to analyze the management of the Qur'an memorization curriculum in improving the quality of student memorization at Raudhatul Athfal. The focus of the study includes aspects of planning, implementation, evaluation, as well as supporting and inhibiting factors in the implementation of the Qur'an memorization curriculum. This study uses a qualitative approach with a library research type, sourced from books, scientific journals, and relevant previous research results. Data collection techniques are carried out through documentation, while data analysis uses the content analysis method with the stages of data reduction, data presentation, and drawing conclusions. The results show that effective Qur'an memorization curriculum management is determined by systematic planning with realistic memorization targets, the implementation of adaptive and enjoyable learning according to the characteristics of early childhood, and continuous evaluation to measure and improve the quality of memorization. In addition, the role of competent teachers and synergy between schools and parents are important factors in maintaining the consistency of student memorization. Supporting factors such as the religious environment and curriculum contribute to strengthening the success of the program, while inhibiting factors such as time constraints and differences in student abilities require appropriate management strategies. Thus, integrated and sustainable management of the Quran memorization curriculum is able to optimally improve the quality of students' memorization, both in terms of quantity and accuracy of reading.